1999
DOI: 10.1002/(sici)1099-0496(199911)28:5<376::aid-ppul10>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy in cystic fibrosis

Abstract: A 17‐year‐old boy and a 12‐year‐old girl with cystic fibrosis (forced expiratory volume in 1 sec, 36% and 14% of predicted values, respectively) developed severe right‐sided lung infections with abscess formations and complete atelectases unresponsive to medical therapy. In both patients, unilateral emergency pneumonectomy resulted in rapid clinical improvement. Despite her severe underlying lung disease, the girl experienced a remarkable increase in quality of life; 2 years after surgery, she died from respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Outcomes in the few cases reported in the literature have varied from death in the early post-operative period 1 through to survival at over four years in one patient. 2 Lung transplantation in unilateral lung destruction raises further difficulties and the optimal approach is not clear. Adhesions around the consolidated, shrunken lung present a considerable technical challenge during lung explantation.…”
Section: Management Of Completed Whole Lung Collapsementioning
confidence: 99%
“…Outcomes in the few cases reported in the literature have varied from death in the early post-operative period 1 through to survival at over four years in one patient. 2 Lung transplantation in unilateral lung destruction raises further difficulties and the optimal approach is not clear. Adhesions around the consolidated, shrunken lung present a considerable technical challenge during lung explantation.…”
Section: Management Of Completed Whole Lung Collapsementioning
confidence: 99%
“…Congenital lesions, benign and malignant tumours and trauma may occasionally require this procedure . Pulmonary resection in patients with cystic fibrosis (CF) has been infrequently reported . In Argentina, the main causes of PNE are sequelae of adenoviral infections.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Pulmonary resection in patients with cystic fibrosis (CF) has been infrequently reported. 7,8 In Argentina, the main causes of PNE are sequelae of adenoviral infections. These patients have severe and extensive lesions with bronchiolitis obliterans (BO) and disseminated bronchiectasis, resulting in irreversible changes in the lung parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the success of conservative medical management, there are circumstances in which surgical therapy for the complications of bronchiectasis may be considered a viable treatment option. The main efforts are to improve quality of life, relieve acute symptoms or as an important salvage for medically refractory disease [37,38]. To date, there is no accepted consensus regarding the surgical management of suppurative lung disease in children with cystic fibrosis.…”
Section: Bronchiectasismentioning
confidence: 99%
“…Surgical resection is a reasonable option in children with severe localized symptomatic bronchiectasis refractory to medical therapy, and should not be considered a contraindication to lung transplantation [41,42]. Hausler et al [38] suggest patients suffering from complete unilateral lung destruction or rapid progressive respiratory failure, or not expected to survive the long wait period for lung transplantation, are candidates for pulmonary resection. More recently, Barlow et al [43] have suggested that heart-lung and double-lung transplantation may be a viable option in patients with cystic fibrosis suffering from end-stage suppurative lung disease, with reported actuarial 5-year survival of 65%.…”
Section: Bronchiectasismentioning
confidence: 99%